PENINGKATAN TINDAK PIDANA ANAK BERUPA PENCABULAN DI PROVINSI D.I. YOGYAKARTA SELAMA MASA PANDEMI COVID-19 - Briantoni, Adnan (Criminal Law Section Faculty of Law Universitas Sebelas Maret, 2023)
This research examines the problem of increasing child crime in the form of obscenity that occurred during the Covid-19 pandemic in the Province of D.I. Yogyakarta. The writing of this law is included in the writing of empirical juridical law. The author emphasizes the existence of legal materials in the form of primary and secondary data obtained by field studies in the form of interviews and literature studies that are relevant to the topic of discussion in research using qualitative analysis. The results of the study show that in the Province of D.I. Yogyakarta The criminal act of obscenity is not only committed by adults, but many students are included in the category of children. In this case, a child who commits a crime must of course be held accountable for his actions and be processed according to applicable legal provisions. The students who were still in the child category committed a criminal act of obscenity during the pandemic due to several factors, one of which was the result of government policy through Kemdikbud Circular Letter No. 15 of 2020 about Guidelines for Learning from Home During the Covid-19 Period. At the time before the Covid-19 pandemic, children carried out face-to-face learning activities carried out at school. He explained that the increase in cases of sexual abuse was one of the impacts caused by the reduced level of parental supervision of children due to the Covid-19 pandemic.